TAX PLANNING, COMPANY SIZE, AND FIRM VALUE IN REAL ESTATE - Andy Adinegara, Ahmad; Fenny Krisdina, Tiana; Damayanti, D'liya; Masruri, Fahrul Alam; Kartika, Tita; Farman, Fanji (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to test and analyze the effect of Tax Planning and Company Size on Company Value in Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) in 2021-2024. By using quantitative research methods, sampling using purposive sampling by means of Judgment sampling, the sample of this study was 12 companies with 48 financial reports. The analysis method used in this research is multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing using the t test and F test. The results in the t test Tax Planning using Effective Tax Rate show that there is a significant negative effect as evidenced by the tcount is smaller than the t table (-2.545 < -2.014). Meanwhile, the t test of Company Size on Company Value has no effect as evidenced by the tcount greater than the ttable value (-0.628> -2.014). The results of the F test show that the Fcount is greater than the Ftabel of (3.389> 3.20), thus together the Tax Planning and Company Size variables have a significant effect on Firm Value in Property and Real Estate companies listed on the IDX in 2021-2024.